Congenital Syphilis: A U.S. Perspective - Alvaro E. Galvis; Antonio Arrieta (MDPI AG, 2020)
Congenital syphilis still represents a worldwide public health problem. If left untreated, it can lead to fetal demise and high neonatal morbidity and mortality. Unfortunately, in the last decade, there has been a resurgence of cases in the U.S. This review discusses the ongoing problem of this preventable congenital infection, vertical transmission and clinical manifestations while providing a guidance for the evaluation and management of infants born to mothers with reactive serologic tests for syphilis.